2008
DOI: 10.1016/j.jpsychires.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity as a moderator of association between smoking status and panic-related processes in a representative sample of adults

Abstract: The present investigation evaluated a moderational role of anxiety sensitivity (fear of anxiety and anxiety-related states; McNally, 2002) in the relation between smoking status and anxiety/depressive symptoms in a Russian epidemiological sample (n = 390; 197 females, Mean age = 43.55). Consistent with prediction, anxiety sensitivity moderated the association of smoking status with indices of anxiety and depressive symptoms; the effects were evident after controlling for the variance accounted for by alcohol u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 69 publications
(77 reference statements)
1
12
0
1
Order By: Relevance
“…However, similar to their findings regarding PA and NA, Zvolensky, Kotov, et al (2008 ) found that AA was unrelated to smoking status in a Russian sample.…”
Section: Relations Between Aa and Smoking Variables Smoking Statussupporting
confidence: 80%
See 2 more Smart Citations
“…However, similar to their findings regarding PA and NA, Zvolensky, Kotov, et al (2008 ) found that AA was unrelated to smoking status in a Russian sample.…”
Section: Relations Between Aa and Smoking Variables Smoking Statussupporting
confidence: 80%
“…Additionally, Morissette, Brown, Kamholz, and Gulliver (2006 ) found that smokers with anxiety disorders reported significantly higher NA than non-smokers with anxiety disorders. Finally, the same study that found PA was not associated with smoking status in Russians also found that NA was not associated with smoking status (Zvolensky, Kotov, et al 2008 ), further suggesting that differences in country of origin may influence the smoking status and affect relationship. …”
Section: Relations Between Na and Smoking Variables Smoking Statusmentioning
confidence: 86%
See 1 more Smart Citation
“…Contrary to this notion, studies have not revealed a relationship between AS and smoking frequency (Novak, Burgess, Clark, Zvolensky, & Brown, 2003;Zvolensky, Kotov, Antipova, & Schmidt, 2003) or status (Zvolensky, Kotov, Bonn-Miller, Schmidt, & Antipova, 2008). In fact, studies have shown that AS is actually positively related to smoking to cope with negative affect (Brown, Kahler, Zvolensky, Lejuez, & Ramsey, 2001;Comeau, Stewart, & Loba, 2001).…”
Section: Anxiety Sensitivity and Substance Usementioning
confidence: 98%
“…Future research would benefit from comprehensive cessation programs including adherence-related skills for NRT and ART, and taking into account the effects of comorbid psychiatric problems, specifically anxiety, in terms of smoking cessation [105,106].…”
Section: Tobaccomentioning
confidence: 99%